Psychosocial Benefits of Cooking Interventions: A Systematic Review - Farmer, Nicole (Health Educ Behav, 2017)
OBJECTIVES: Cooking interventions are used in therapeutic and rehabilitative settings; however, little is known about the influence of these interventions on psychosocial outcomes. This systematic review examines the research evidence regarding the influence of cooking interventions on psychosocial outcomes. METHODS: A systematic review of the literature examined peer-reviewed research using Embase, PubMed, CINALH Plus, and PsychInfo with the following search terms: cooking, culinary, baking, food preparation, cookery, occupational therapy, mental health, mood, psychosocial, affect, confidence, self-confidence, self-esteem, socialization, and rehabilitation. Inclusion criteria were the following: adults, English, influence of cooking interventions on psychosocial outcomes. PRISMA guidelines were used. RESULTS: The search yielded 377 articles; and 11 ultimately met inclusion criteria and were reviewed. Generally, the quality of the research was weak due to nonrandomization, unvalidated research tools, and small sample sizes. However, inpatient and community-based cooking interventions yielded positive influences on socialization, self-esteem, quality of life, and affect. CONCLUSIONS: Finding benefits to cooking that extend beyond nutritional may be helpful in increasing motivation and frequency of cooking. This review suggests that cooking interventions may positively influence psychosocial outcomes, although this evidence is preliminary and limited. Further qualitative and rigorous quantitative research are needed to identify mechanisms by which cooking interventions may improve psychosocial outcomes.